An Al2O3 coating layer on mesoporous Si nanospheres for stable solid electrolyte interphase and high-rate capacity for lithium ion batteries. Issue 36 (30th August 2019) - Li, Na; Yi, Zheng; Lin, Ning; Qian, Yitai
Abstract : A simple and one-pot replacement reaction route was designed to produce an Al2 O3 layer anchored on mesoporous Si nanospheres by employing Al nanospheres with a naturally formed Al2 O3 layer as a reducing agent and self-sacrificial template. Abstract : The application of Si-based anode materials is hindered by their extreme volume change, poor cycling stability, and low coulombic efficiency. Solving these problems generally requires a combination of strategies, such as nanostructure designing or surface coating. However, these strategies increase the difficulty of the fabrication process. Herein, a simple and one-pot replacement reaction route was designed to produce an Al2 O3 layer anchored on mesoporous Si nanospheres (Si@Al2 O3 ) by employing Al nanospheres with a naturally formed Al2 O3 layer as a reducing agent and self-sacrificial template. The obtained Si@Al2 O3 was mesoporous, with enough porous space to buffer the volume change and provide a fast lithium ion transfer channel. Furthermore, the coated Al2 O3 layer could stabilize the structure and SEI layer of the mesoporous Si nanospheres, endowing the Si@Al2 O3 nanospheres with improved initial coulombic efficiency, cycling performance and rate capability. As a result, a high capacity of 1750.2 mA h g −1 at 0.5 A g −1 after 120 cycles and 1001.7 mA h g −1 at 2 A g −1 after 500 cycles were delivered for lithium ion batteries. The good performance could be attributed to the mesoporous structure and the outer-coated Al2 O3 layer.